The Effect of Classical Guidance Services Using the Jigsaw Cooperative Learning Model on Students’ Self-Regulation at SMA Negeri 8 Medan - Melva Triana Sembiring; Abdul Murad (Cakrawala Sekolah: Journal of Multidisciplinary School Education, 2026)
Self-regulation is an essential factor that influences students’ ability to manage their learning processes effectively and achieve academic success. However, preliminary observations conducted at SMA Negeri 8 Medan indicated that many students demonstrated low levels of self-regulation, as reflected in poor time management, procrastination, low learning motivation, and limited responsibility toward academic tasks. This study aimed to examine the effect of classical guidance services using the Jigsaw cooperative learning model on students’ self-regulation in learning. The study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The participants consisted of 36 students from Class XI-8 at SMA Negeri 8 Medan, selected through purposive sampling based on preliminary assessments indicating low self-regulation levels. Data were collected using a self-regulation questionnaire developed based on Zimmerman’s theory, encompassing planning, self-monitoring, self-control, and self-evaluation dimensions. The instrument demonstrated excellent reliability with a Cronbach’s Alpha coefficient of 0.917. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and a paired-samples t-test. The results revealed that the mean self-regulation score increased from 82.22 in the pretest to 99.58 in the posttest, representing an average improvement of 17.36 points or approximately 21%. Furthermore, the paired-samples t-test indicated a statistically significant difference between pretest and posttest scores (p < .001). These findings demonstrate that classical guidance services utilizing the Jigsaw cooperative learning model effectively enhance students’ self-regulation in learning. The study suggests that integrating cooperative learning strategies into guidance and counseling services can promote students’ responsibility, independence, and active engagement in learning.